2004
DOI: 10.1007/s00232-004-0711-x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Conserved Acidic Residues in MntH, the Nramp homolog of Escherichia coli

Abstract: A bioinformatic approach was used for the identification of residues that are conserved within the Nramp family of metal transporters. Site-directed mutagenesis was then carried out to change six conserved acidic residues (i.e., Asp-34, Glu-102, Asp-109, Glu-112, Glu-154, and Asp-238) in the E. coli Nramp homolog mntH. Of these six, five of them, Asp-34, Glu-102, Asp-109, Glu-112, and Asp-238 appear to be important for function since conservative substitutions at these sites result in a substantial loss of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 37 publications
5
50
0
Order By: Relevance
“…1C). Loss of a metal-coordinating residue that uses oxygen to bind the metal, D56 or N59, was detrimental to Co 2+ uptake, consistent with the previously demonstrated importance of these residues to the transport of Co 2+ , Fe 2+ , Mn 2+ , and Cd 2+ in bacterial and eukaryotic Nramp homologs (9,(17)(18)(19)(20).…”
Section: Significancesupporting
confidence: 84%
“…1C). Loss of a metal-coordinating residue that uses oxygen to bind the metal, D56 or N59, was detrimental to Co 2+ uptake, consistent with the previously demonstrated importance of these residues to the transport of Co 2+ , Fe 2+ , Mn 2+ , and Cd 2+ in bacterial and eukaryotic Nramp homologs (9,(17)(18)(19)(20).…”
Section: Significancesupporting
confidence: 84%
“…The TM location of the targeted sites is schematized (Fig. 1A) based on previous predictions and experimental determinations (11,14,15,39). The mutant proteins displayed membrane expression levels similar to MntH-WT, indicating that the substitutions were structurally well tolerated (Fig.…”
Section: Methodsmentioning
confidence: 88%
“…The TMS1 Asp residue is part of a conserved DPGN motif that has been subjected to mutagenesis in studies using MntH or Nramp2 homologs, which showed loss of Me 2ϩ uptake caused by Gly exchange (11,47). The carboxyl end of Nramp2 TMS1 and adjacent extra loop were implicated in Me 2ϩ binding and coupling of Me 2ϩ uptake to the proton-motive force ((C/S/T)P(C/H)) that is conserved in the TMS6 of P 1B -type ATPases, which pump heavy metal cations using energy provided by ATP hydrolysis (48,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that Glu129 is not the primary H þ acceptor during transport. Still, since at lower pH, the corresponding mutation of the E. coli homologue MntH strongly decreased the rate of Mn 2 þ uptake into cells 40 , this residue probably plays an important role for protein function.…”
Section: Discussionmentioning
confidence: 99%